Implementasi Asuransi Syariah Bagi Nelayan (Studi Kasus Desa Penebal Kecamatan Bengkalis) - Laila Ramadhona; Nirwana Nirwana; Muhamad Aji Purwanto (JOURNAL OF SHARIA ECONOMICS, 2024)
Implementation of Sharia Insurance for Fishermen (Case Example: Fishermen in Penebal Village, Bengkalis, Riau). The purpose of this study is to assess the application of Sharia Insurance for Fishermen in Penebal Village, and to recognize the factors that facilitate or impede its effectiveness. Researchers employed qualitative descriptive methods to conduct field research. The techniques for gathering data included conducting interviews and collecting documents. The research employs an interactive approach developed by Miles and Huberman for data analysis. This approach includes data reduction, data presentation, and data conclusion stages. Problems in the implementation were caused by, among others, the lack of clarity of information, the lack of completeness of information, and the lack of thinking ability possessed by fishermen. This has hindered the integration of the program. George Edwards stated that there are four indications that indicate the execution. This has hindered the interaction of the program. According to George Edwards, there are four indications that indicate the execution. One of these factors is communication. The Bank Syariah Indonesia (BSI) branch in Bengkalis conducted an event to launch a new program for fishermen. There is a shortage of human resources, particularly staff, which is causing delays in the data collection and verification process for the fishermen. However, the implementers have shown a positive attitude towards the policy of providing protection guarantee for the risk of work accidents for fishermen, in accordance with the KKP technical guidelines' Standard Operating Procedures (SOP). Challenges in implementing the protection program for fishermen include a lack of engagement from fishermen in realizing the significance of safeguarding against the potential for accidents, as well as a deficit in personnel carrying out the policy for preventing occupational accidents among fishermen.